Pengaruh Penerapan Akuntansi Forensik Dan Audit Investigatif Dalam Mendeteksi Kecurangan Pengadaan Barang Dan Jasa (International Forum of Researchers and Lecturers, 2023)
This study is intended to determine the effect of applying forensic accounting and investigative auditing in detecting fraud in the procurement of goods or services at BPKP Representatives of South Sumatra Province, either partially or simultaneously. Forensic accounting and investigative auditing are solutions for detecting cases of fraud in Indonesia, one of which is fraud in the procurement of goods or services. This study was a quantitative research category and data were analyzed using the Multiple Linear Regression analysis technique using the help of the IBM SPSS version 23 application. The population in the study were all auditors working at the BPKP Representative for South Sumatra Province while the sample was 46 auditors and this study used a purposive sampling type. The results of this study indicate that partially and simultaneously forensic accounting and investigative auditing have a significant positive effect on detecting fraud in the procurement of goods or services at BPKP Representatives of South Sumatra Province. Based on the results of this study, it can be concluded that the better the application of forensic accounting and investigative auditing at the BPKP Representative of South Sumatra Province, it will have a positive effect on increasing the success of detecting fraud by the auditor.